THE EFFECT OF THICKNESS ON DC CONDUCTIVITY AND OPTICALENERGY GAP OF (A–GE ) THIN FILM - Al-Essa, Izzat M; Hamadi, Talib Saloom (Al-Nahrain Journal of Science, 2009)
The films of amorphous germanium (a–Ge) were prepared by thermal evaporation under high vacuum conditions (10-6 ) torr. The influence of various thickness (1000–5000 ) Ǻ on the d.c electrical conductivity (σRT) at 303K and optical energy gaps (Eg) of (a – Ge ) was studied.The temperature dependence of conductivity for various thickness recorded in the range (303–503) K consisted of two regions, medium and high temperature regions. It’s found that the results of the energy gap decrease from 1.05 eV to 0.86 eV.as the thickness increase from 1000 Ǻ to 5000 Ǻ respectively while d.c conductivity (σRT) increase from 3.0510-4(Ω.cm)-1 to 2.209103 (Ω.cm)1 respectively with the same variation of thickness.